implementasi implementasi sistem penjaminan mutu internal - Afdah Afdah; Anggra Prima; Anita Yulfiah; Kader Kopo Lonek (BEduManagers Journal : Borneo Educational Management and Research Journal, 2026)
The Internal Quality Assurance System (IQAS) is a strategic instrument for improving educational quality, particularly at the primary education level. The implementation of IQAS is essential to ensure the systematic and sustainable achievement of the National Education Standards. This study aims to analyze the implementation of IQAS at SDN 002 Sangatta Selatan in terms of organizational structure, application of standard operating procedures, resource management, and quality improvement programs. This study adopted a qualitative descriptive methodology using a case study design. Data were collected through in-depth interviews with the principal as the key informant and analyzed using descriptive qualitative techniques. The findings indicate that IQAS implementation is carried out through the establishment of a quality assurance team involving all school components, participatory development of standard operating procedures, implementation of the Merdeka Curriculum through standardized teaching modules, and the development of strategic partnerships with external stakeholders. The school also implements continuous quality improvement programs, although it still faces limitations in infrastructure and challenges in providing inclusive education services. Overall, the implementation of IQAS at SDN 002 Sangatta Selatan has been conducted systematically and collaboratively; however, further strengthening is required in the areas of facilities and inclusive education.